2021
DOI: 10.1111/1756-185x.14104
|View full text |Cite
|
Sign up to set email alerts
|

The pathophysiological effects of exercise in the management of idiopathic inflammatory myopathies: A scoping review

Abstract: Idiopathic inflammatory myopathy (IIM) is a term used for a heterogeneous group of diseases characterized by severe muscle weakness. In addition to pharmacological treatment options, non‐pharmacological methods such as exercising are essential for proper management of myositis. The present article aimed to provide an insight into the potential pathophysiological mechanisms underlying exercise‐related benefits in myositis. A systematic search was performed on PubMed/MEDLINE, Scopus, Web of Science, and Google S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…There are currently several mechanisms regarding exercise-induced benefits, which include exercise increases microcirculation and mitochondrial function, which results in a significant ameliorative function for muscle, [ 23 , 24 ] physical activity reduces a variety of inflammatory responses through immunomodulatory effects, [ 25 ] exercise effectively reduces muscle fibrosis, [ 26 ] exercise induces a reduction in endoplasmic reticulum stress, which prevents and prevents muscle degeneration and expression of malignant factors, [ 27 , 28 ] and another point is that exercise enhances cardiorespiratory adaptations, which are significantly negatively correlated with all-cause mortality. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are currently several mechanisms regarding exercise-induced benefits, which include exercise increases microcirculation and mitochondrial function, which results in a significant ameliorative function for muscle, [ 23 , 24 ] physical activity reduces a variety of inflammatory responses through immunomodulatory effects, [ 25 ] exercise effectively reduces muscle fibrosis, [ 26 ] exercise induces a reduction in endoplasmic reticulum stress, which prevents and prevents muscle degeneration and expression of malignant factors, [ 27 , 28 ] and another point is that exercise enhances cardiorespiratory adaptations, which are significantly negatively correlated with all-cause mortality. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…There are currently several mechanisms regarding exercise-induced benefits, which include exercise increases microcirculation and mitochondrial function, which results in a significant ameliorative function for muscle, [23,24] physical activity reduces a variety of inflammatory responses through immunomodulatory effects, [25] exercise effectively reduces muscle fibrosis, [26] exercise induces a reduction in endoplasmic reticulum stress, which prevents and prevents muscle degeneration and expression of malignant factors, [27,28] and another point is that exercise enhances cardiorespiratory adaptations, which are significantly negatively correlated with all-cause mortality. [29] As "lack of time" is often cited as the most common barrier to increasing habitual physical activity, recent years have seen a renewed interest in "time-efficient" physical activity, [30] typically short, high-intensity exercise that triggers acute activation of signaling pathways [31] and Cardiovascular, mitochondrial and metabolic adaptations [32,33] are similar to those of more traditional low-intensity, endurance exercise programs.…”
Section: Mechanisms Of the Benefits Of Exercisementioning
confidence: 99%
“…The increase in CK blood levels with consequent normalization after 24 hours is a normal acute response to exercise, but there are no studies that support this idea [ 4 ]. A review by Benlidayi et al [ 7 ] found that exercise has a positive impact on idiopathic, autoimmune, and non-autoimmune myositis. These benefits include increased enzyme activity, mitochondrial biogenesis, reconditioning of inflammatory/immune pathways, decreased endoplasmic reticulum stress, modulation of gene expression, increased protein synthesis and cytoskeletal remodeling, and decreased muscle fibrosis and infiltration in nonmuscular tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity provides immunomodulatory effects. Regular exercise training can induce immune competence [38]. Given the impact of exercising on psychological health, older adults might use exercise as a coping strategy [39,40].…”
Section: The Effects Of Various Exercise Types On Psychological Healthmentioning
confidence: 99%